Diastolic Dysfunction in Normotensive Patients with Diabetes Mellitus - A Double Blind Randomised Prospective Multicentre Study in North India (Global Journal of Medical Research, 2020)
Aim: To study the Ventricular function of Older Patients with diabetes but without hypertension. Type of Study: Prospective Analysis. Methodology: 2500 Patients diagno sed as suffering from Diabetes Mellitus (either type 1or type 2), who were normotensive but older than 18 years and visited Medicine or Cardiology Out Patient Departments in four different hospitals, were included in the study. All the patients were subjected to a detailed history and clinical examination. The mean age of patients was 48.8yrs. 55.4 % were Males, 44.4 % were Females and, 0.2 % were not otherwise specified. Patients underwent a battery of tests including, Echocardiography. Results: In our Stud y, 72 % of the patients had diabetes for a duration of less than ten years and, 28 % of the patients had more than ten years. 20% had Body Mass Index within Normal Range but Impaired in remaining 80%.
Keywords: diabetes; hypertension; echocardiography; ventricle